Factors influencing the dispersion of Arceuthobium oxycedri in Central Spain: evaluation with a new null model for marked point patterns - Ramon Contento, P. (2017)
The dwarf mistletoe, Arceuthobium oxycedri, is found on populations of Juniperus oxycedrus, in central Spain. This species can have negative effects on the physiology of its host, including mortality. Understanding the mechanisms that control its distribution and dispersal is critical to assessing its potential for spread. We assessed dwarf mistletoe distribution within a population of J. oxycedrus, including infected and uninfected host individuals. A new null model of parasitic dispersion was built using two dispersal kernel forms that were simulated with lower and upper envelopes for second-order functions to summarize a point pattern, such as Ripley's K, nearest-neighbour distribution and pair correlation functions. Nine dispersal scenarios were constructed with half-bandwidth kernels (10, 20, 30 m) and initial population of infected trees (P0 = 05, 10 and 20). These scenarios were compared with the observed pattern and evaluated using the goodness-of-fit test. Significant differences at short distance (r < 10 m) were found between the observed pattern and simulated patterns, corresponding to the range of seed dispersal of the dwarf mistletoe. Interactions between infected and uninfected hosts patterns at all scales were identified, suggesting that A. oxycedri uses other mechanisms in addition to ballistic seed shooting as secondary dispersal agents to spread to distances greater than 20 m. Given that the seed characteristics facilitate dispersal by adhesion, we infer that spread between host individuals is amplified by seed transport by birds or small mammals.